Differential Sensitivity of Male and Female Neuronal cells May Play a Role in Onset of Neuronal Diseases - T Entezari Zaher; F Etesam; M Javdan; A Sobhani; M Akbari; RA Lockshin; Z Zakeri (Tehran University of Medical Sciences, 2005)
Due to the worldwide increase in the number of older people in both developed and developing countries, there is a public health concern for dealing with age related diseases such as neurodegenerative diseases. There is little known about the difference in neuronal cell responses between genders. Our understanding of the neuronal cell response regarding genders, will be useful for developing more efficient therapies for these diseases such as Alzheimer's disease. To investigate gender differences in neuronal cell response against cell death inducers, we examined the percentage of cell death in male and female mouse primary cortical neuronal cultures. Our findings indicate that there is a difference in cellular response to ethanol (a cell death inducer) that may be the basis of how they behave in vivo of what may be seen in adults, as they age. These observation support this idea that genetic factors, most likely governed by X or Y chromosomes.